Selective one-pot multicomponent synthesis of N-substituted 2,3,5-functionalized 3-cyanopyrroles via the reaction between α-hydroxyketones, oxoacetonitriles, and primary amines - Xia, Mengxin (2023)
A one-step, three-component reaction between α-hydroxyketones, oxoacetonitriles, and primary amines gives N-substituted 2,3,5-functionalized 3-cyanopyrroles with complete selectivity in up to 90% isolated yields. The reaction worked on a wide substrate scope under mild reaction conditions (AcOH as a catalyst, EtOH, 70 °C, 3 h). The reaction proceeded with very high atom efficiency as water is the only molecule lost during the reaction. The practicality of the reaction was demonstrated on a large gram scale. The structures of the 3-cyanopyrroles were confirmed by single-crystal X-ray diffraction and NMR; this work provides a general and practical entry to pyrrole scaffolds suitably decorated for the synthesis of various bioactive pyrroles in a concise manner.